Les installations immersives muséalisées : un défi muséographique. Connaître l’expérience des visiteurs pour adapter l’accompagnement muséal. - Elizabeth Desbans (Les Cahiers de l'École du Louvre)
Immersive museum installations: a museographic challenge. Knowing the visitor’s experience to adapt the museum experience. Case study: the Musée National d’Art Moderne et Contemporain, Centre Georges-Pompidou. Installation art emerged in a climate of protest against the institution of the museum in the 1950s and 1960s. The works were therefore not originally intended to be exhibited in museums. Today, their integration into permanent collections presents multiple challenges relating to conservation, museography and mediation. The link between these issues is the public. This article, which is part of a larger research project conducted at the Musée National d’Art Moderne (MNAM) in 2019, aims to analyse the experience of young adult visitors to immersive museum installations through a qualitative study of audiences: How is their experience characterised? Are there different forms of immersion? What role can the wall label play in immersion ?